Integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) in Education in the Era of Technology - Mia Andriyani (PT. Mifandi Mandiri Digital, 2024)
This study aims to analyze the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning model in enhancing students' creativity at SMP Swasta Darma. The research method employed is a literature review, examining various references related to the application of the STEAM model in the context of education and creativity. Data were collected through document analysis, which includes previous research, articles, books, and other relevant sources. The findings reveal that the implementation of the STEAM model can enhance students' creativity, measured through indicators such as idea flow, creative thinking ability, cognitive flexibility, and appreciation for art and innovation. The STEAM model allows students to develop creative thinking skills through interdisciplinary learning experiences and complex problem-solving. Additionally, the application of this model encourages collaboration among students in team projects, enabling them to exchange ideas and work together in developing innovative solutions. Overall, the study concludes that the STEAM learning model is effective in enhancing students' creativity and recommends further development of STEAM implementation in formal education.